Age and conditions of the formation of the buried soils in the Stajki section by palynological studies - Yelovicheva, Yadviga K. (Journal of the Belarusian State University. Geography and Geology, 2017)
In the article are set forth materials of the palynological researches of the soil sediments in the section et the vil. Stajki (Mogilev Podniepr, Belarus), the age of which is dated Holocene interglacial (isotopic stage 1). Characterized spectra clearing composition 1 (phase SA-1, 2, 3) and 2 (early Holocene: PB-1, BO-2; Middle Holocene: AT-1, 2, 3; Late Holocene: SB-1, 2; SA-1, 2, 3), the character of the vegetation of paleolandscapes (pine forests with birch → pine forests with meso- and thermophilic breeds → broad-leaved forest (linden, oak-elm and then hornbeam and hornbeam forests, alder) → spruce and pine forests with meso- and thermophilic breeds → pine with spruce and birch), especially palynoflora (rare-seldom in the Holocene optimum Abies alba, Larix, Nymphaea alba, Salvinia natans), dynamics of palaeolake (the riverbed in the Late Glacial and early Holocene – 13 900–10 000 y. a., overgrown of riverbed in predoptimum time – 8400–8800 y. a., marsh regime in the Holocene optimum – 8000–5300 y. a., renewal of river flow from the end of optimum (AT-3-d) to the beginning SB – 4700–5300 y. a. in the steady slow mode, and in a more dynamic – in SB-1, SB-2 – 1600– 4700 y. a., soil development in the SA-3 (1600 y. a. – present)) and paleoclimate (cool and dry, then moderately-warm and dry in predoptimum time, warm and humid in the Holocene optimum, moderately-warm and humid, the change of moderately-warm and dry in postoptimum time) of the selected stages.
Keywords: palynology; Holocene; vegetation; buried soils; climate; Holocene interglaciation